Illness representations in chronic diseases: A literature review - Rahayu, Sri; Rahayuningsih, Faizah Betty; Indriyani, Yeni; Azkiya, Arifatul; Baety, Nimas Citra Nur; Pratiwi, Jiheny Siska (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2023)
The prevalence of chronic illnesses, including hypertension, stroke, heart failure, diabetes mellitus, cancer, and chronic kidney disease, is rising globally. The primary causes of death and disability among patients are these kinds of illnesses. Consequently, healthcare professionals must focus more on these illnesses. This study aims to collect and examine articles related to illness representations in chronic diseases. A search for relevant literature was conducted using the following keywords: "Illness Representations," "Female," "Patient," and "Chronic Diseases" across three databases: PubMed, Taylor Francis, and Science Direct. Time for articles with searches published from 2018 to 2023. Five articles were selected after screening 762 total articles in accordance with the PRISMA flowchart guidelines. The findings indicated that different populations have different representations of chronic diseases and that these diseases are reflected in the course of illness. It is important to take into account various factors that influence the way illnesses are portrayed, including stable health conditions, knowledge, perception, the duration of the illness, and marital satisfaction. It should be possible for future research to examine how illnesses are represented as chronic diseases in greater detail using a range of research designs.Abstrak: Prevalensi penyakit kronis, termasuk hipertensi, stroke, gagal jantung, diabetes melitus, kanker, dan penyakit ginjal kronis, meningkat secara global. Penyakit ini merupakan penyebab utama kematian dan kecacatan pada pasien. Oleh karena itu, tenaga kesehatan harus lebih fokus pada penyakit ini. Penelitian ini bertujuan untuk mengumpulkan dan mengkaji artikel tentang representasi penyakit pada pasien dengan penyakit kronis. Pencarian literatur yang relevan dilakukan dengan menggunakan kata kunci berikut: "Illness Representations", "Female", "Patient", dan "Chronic Diseases" di tiga database: PubMed, Taylor Francis, dan Science Direct. Rentang waktu pencarian artikel yang dipublikasikan mulai pada tahun 2018 hingga 2023. Lima artikel terpilih setelah menyaring dari total 762 artikel sesuai dengan pedoman flowchart PRISMA. Hasil review menunjukkan bahwa populasi yang berbeda memiliki gambaran penyakit kronis yang berbeda, dan penyakit ini tercermin dari perjalanan penyakitnya. Penting untuk mempertimbangkan berbagai faktor yang mempengaruhi representasi penyakit, termasuk kondisi kesehatan yang stabil, pengetahuan, persepsi, durasi penyakit, dan kepuasan pernikahan. Penelitian selanjutnya dapat meneliti bagaimana representasi penyakit pada pasien dengan penyakit kronis secara lebih rinci dengan menggunakan serangkaian desain penelitian.